Experimental study on mechanical behavior of laterite soil treated with quicklime / Roslizayati Razali ... [et al.] - Razali, Roslizayati; A. Rashid, Ahmad Safuan; Hezmi, Muhammad Azril; Roshan, Mohammad Jawed; Zakaria, Nur Syahirah Syuhadah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2022)
The present study examines the effect of lime stabilisation on the mechanical properties of laterite soil. Compaction tests were performed in order to obtain optimum moisture content (OMC) and maximum dry density (MDD) for untreated and lime treated laterite soil. A series of Unconfined compressive strength (UCS) tests were carried out on the specimen containing different percentages of lime. In preparing test specimens, laterite soil was initially compacted at their respective OMC and MDD conditions and allowed to cure for 0, 3, 7, 14 and 28 days before being tested. Results for the standard compaction test show an increasing trend for optimum moisture content (OMC), whereas maximum dry density (MDD) decreased as the concentration of lime increased. On the other hand, UCS results indicated that all percentages of lime treated laterite increased in strength with the curing period.